The influence of Malays' social hierarchy in the implementation of a western-based participatory action research project in Malaysia / Fariza Puteh Behak … [et al.] - Behak, Fariza Puteh; Massari, Norhaili; Harun, Haliza; Abdul Hamid, Yurni Emilia (Division of Research and Industry Linkages, UiTM Melaka, 2014)
In sustaining excellence in a globalized Malay and Islamic world, it is important to investigate the influence of the Malays cultural background in many areas including in the area of researching. This paper was part of a larger study that investigated the influence of Malays values and culture in conducting a participatory action research project in Malaysia. The participatory action research project, which originated from the Western philosophy; was conducted by a research team, which consisted of the first author of the current paper and two Malay lecturers from Bakti Polytechnic (pseudonyms). Through qualitative methods such as observation, informal conversations, journal reflections and semi-structured interviews, this study investigated the experiences of the two Malay lecturers in negotiating the Western based concepts in a participatory action research project. Due to the importance of reflection and action in a participatory action research, data was analysed through a Critical Reflective-Analysis Steps (Puteh-Behak, 2013) which included the process of observing and noting personal reflections, confronting and thinking, and taking action. Findings suggest that the Malay lecturers' social hierarchy background affected the way they negotiated the Western-based egalitarian concept in participatory action research.